2016
DOI: 10.11138/jpm/2016.10.3.023
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of procalcitonin or c-reactive protein for subclinical intrauterine infection in patients with premature rupture of membranes (PROM)

Abstract: Introduction: to evaluate the diagnostic value of procalcitonin (PCT) and C-reactive protein (CRP) for the prediction of subclinical intrauterine infection in patients with premature rupture of membranes (PROM). Methods: a retrospective analysis was performed based on patients with PROM admitted into our hospital between January 2011 and January 2016. Using the pathological diagnosis of placenta as the gold standard, the sensitivities, specificities, positive predictive values, and negative predictive values o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, data in non‐pregnant women should be extrapolated with caution to pregnant women and further prospective data are needed. A retrospective analysis indicated that the sensitivity and specificity of PCT is superior to CRP for the diagnosis of intrauterine infections in pregnant women with pre‐labor rupture of membranes .…”
mentioning
confidence: 99%
“…However, data in non‐pregnant women should be extrapolated with caution to pregnant women and further prospective data are needed. A retrospective analysis indicated that the sensitivity and specificity of PCT is superior to CRP for the diagnosis of intrauterine infections in pregnant women with pre‐labor rupture of membranes .…”
mentioning
confidence: 99%
“…A study by Li et al ( 100 ) evaluated the diagnostic value of CRP and procalcitonin (PCT) levels in maternal serum to predict the subclinical intrauterine infection in pregnant women with pPROM at < 34 gestational weeks and found them with good application potential. Moreover, they found PCT more applicable to pregnant women with pPROM between 28 to 33+6 gestational weeks ( 100 ). Likewise, Caloone et al ( 101 ) found CRP the best maternal marker for predicting histological chorioamnionitis after pPROM.…”
Section: Emerging Markers For Predicting Pprom and Chorioamnionitis In Women With Pprommentioning
confidence: 99%
“…evaluated the diagnostic value of procalcitonin and CRP for the prediction of suclinical intrauterine infection in patients with P‐PROM. Both parameters are good predictive and diagnostic indicators for PROM associated with chorioamnionitis, and procalcitonin is more suitable for pregnant women at 28–33 +6 weeks . Moreover, amniotic fluid interleukin‐6 (IL‐6) and tumor necrosis factor‐α (TNF‐α) seem to be good predictors for fetal inflammatory response syndrome and may improve the clinical management of patients with P‐PROM.…”
Section: Prediction Of P‐prom and P‐prom/preterm Delivery Latencymentioning
confidence: 99%
“…45 citonin is more suitable for pregnant women at 28-33 +6 weeks. 47 Moreover, amniotic fluid interleukin-6 (IL-6) and tumor necrosis factorα (TNFα) seem to be good predictors for fetal inflammatory response syndrome and may improve the clinical management of patients with P-PROM. The non-invasive technique of sampling amniotic fluid from vaginal secretions facilitates daily measurements and bedside assessment of cytokines, and is in this respect preferable to invasive amniocentesis.…”
Section: Mehra Et Al Demonstrated That a Shorter Transvaginal Cervicalmentioning
confidence: 99%